Transcranial Direct Current Stimulation Does Not Affect Lower Extremity Muscle Strength Training in Healthy Individuals: A Triple-Blind, Sham-Controlled Study - Maeda, Kazuhei; Yamaguchi, Tomofumi; Tatemoto, Tsuyoshi; Kondo, Kunitsugu; Otaka, Yohei; Tanaka, Satoshi (Frontiers in Neuroscience, 2017)
The present study investigated the effects of anodal transcranial direct current stimulation (tDCS) on lower extremity muscle strength training in 24 healthy participants. In this triple-blind, sham-controlled study, participants were randomly allocated to the anodal tDCS plus muscle strength training (anodal tDCS) group or sham tDCS plus muscle strength training (sham tDCS) group. Anodal tDCS (2 mA) was applied to the primary motor cortex of the lower extremity during muscle strength training of the knee extensors and flexors. Training was conducted once every 3 days for 3 weeks (7 sessions). Knee extensor and flexor peak torques were evaluated before and after the 3 weeks of training. After the 3-week intervention, peak torques of knee extension and flexion changed from 155.9 Nm to 191.1 Nm and from 81.5 Nm to 93.1 Nm in the anodal tDCS group. Peak torques changed from 164.1 Nm to 194.8 Nm on extension and from 78.0 Nm to 85.6 Nm on flexion in the sham tDCS group. In both groups, peak torques of knee extension and flexion significantly increased after the intervention, with no significant difference between the anodal tDCS and sham tDCS groups. In conclusion, although the administration of eccentric training increased knee extensor and flexor peak torques, anodal tDCS did not enhance the effects of lower extremity muscle strength training in healthy individuals. The present null results have crucial implications for selecting optimal stimulation parameters for clinical trials.